Un puzzle chartrain: mettre en ordre les fragments d’une anthologie théologique d’œuvres rares - Dominique Poirel (Scrineum Rivista, 2020)
A Chartrain puzzle: putting in order the fragments of a theo- logical anthology of rare and out-of-date texts. By its material state and intellectual content, the ms. Chartres, Mediathèque l’Apostrophe, 205 (3rd qu. of 13th c., from the Cathedral Chapter of Chartres) is a good example of the procedures that were followed at Institut de Recherche et d’Histoire des Textes (CNRS, Paris), to put the Chartres manuscripts back in order, after their leaves were gnawed and unbound by the flame in 1944. Based on the surviving folios and on the documentation prior to the fire, electronic concordances are used whenever possible to iden- tify the text of the folios. Then these are put back in orderly series, and finally their foliotation is reconstructed by comparison with the cata- logues. The result allows some previous identifications to be corrected or completed. In the case of ms. 205, a historical question then arises: why does this manuscript, probably bequeathed by a canon of Chartres cathedral, contain such an unusual choice of texts, in particular a selec- tion of pre-scholastic works (Anselm of Cantorbery, Odo of Tournai, Ul- ger of Liège, Hildebert of Lavardin, Hugh and Richard de Saint-Victor, Bernard of Clairvaux, Honorius Augustodunensis), although they were out of fashion in the second half of the 13th century? And why does the ms. transcribe in this context a mysterious treatise “Against those who do not believe in the future life”, of which only a few vestiges remain ? Reproductions are available online at https://bvmm.irht.cnrs.fr/ and the description at https://www.manuscrits-de-chartres.fr/.